Controversial Concept Regarding Apostle’s Characterization in The Bible and The Qur’ān - Khan Sherwani, Awais uddin; Hussain, Taswar (Al-Amīr Research Journal for Islamic Studies, 2024)
When studying the Bible, we come across several accusations made against prophets and Allah’s apostle, who has noted that there is no distinction between layman and prophets. The Bible claims that an apostle is capable of committing any form of sin that a common person is. However, the Quran tells of a Prophet who possesses an elevated, big, good, and outstanding character that the others might not. We fervently believe that a comparison between the descriptions found in the Bible and the Quran should be made, leaving it up to the readers’ intelligence to make the final determination, based on an analytical analysis of both texts. The concept of prophetic immaculacy is absent from the Bible, yet it is explicitly depicted in the Quran. Not only is there Muhammad, but every one of Allah’s apostles is pure. They are located far from vices. Numerous prophets are implicated in different deadly crimes, including as polytheism, rape, backbiting, murder, drinking, robbery, dodging, fraud, cheating, and corruption, according to the Bible. It is with great regret that we must state that if prophets are involved in such terrible sins that damage society’s beauty, then who would prosper and ensure that the community commits wrongdoings? Bible places numerous charges on prophets like Noah, Moses, Joseph, and Loot. Solomon, David, Aaron, Jacob, and so forth. Keywords: Chastity of Prophets, Quran and Bible, Apostle’s innocence